2009
DOI: 10.1093/schbul/sbn162
|View full text |Cite
|
Sign up to set email alerts
|

Working memory and DLPFC inefficiency in schizophrenia: The FBIRN study

Abstract: The increase in BOLD signal change from minimal to moderate memory loads was greater in the schizophrenic subjects than in controls. This effect remained when age, gender, run, hemisphere, and performance were considered, consistent with inefficient DLPFC function during working memory. These findings from a large multisite sample support the concept not of hyper- or hypofrontality in schizophrenia, but rather DLPFC inefficiency that may be manifested in either direction depending on task demands. This redirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
255
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(289 citation statements)
references
References 63 publications
33
255
1
Order By: Relevance
“…Healthy controls had a mean verbal IQ of 110 (SD, Ϯ10.50) and a mean of 15 years of education (SD, Ϯ3.70). As in previous studies, verbal IQ was significantly higher in healthy controls, as were years of education (Potkin et al, 2009;Morris et al, 2011).…”
Section: Participants and Instrumentssupporting
confidence: 85%
“…Healthy controls had a mean verbal IQ of 110 (SD, Ϯ10.50) and a mean of 15 years of education (SD, Ϯ3.70). As in previous studies, verbal IQ was significantly higher in healthy controls, as were years of education (Potkin et al, 2009;Morris et al, 2011).…”
Section: Participants and Instrumentssupporting
confidence: 85%
“…[4][5][6][7][8][9][10]44,45 Part of the importance of the present investigation is that it shows that frontal functional connectivity changes involving the inferior frontal gyrus are present in FE, antipsychoticnaive patients. A recent review 2 of functional connectivity changes in schizophrenia involved typically much smaller sample sizes than those reported here, and reported typically altered functional connectivity in patients sometimes involving the frontal lobe, but without much emphasis on the thalamus, and with no marked stage-specific differences in functional connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of schizophrenia involves distributed functional dysconnectivity involving a number of brain regions, 1,2 including the frontal lobe, [3][4][5][6][7][8][9][10] and its language-related areas in the inferior frontal gyrus, 11,12 sensory-motor areas, 13 the temporal lobe, 14 limbic structures, 15,16 and thalamus. [17][18][19][20][21][22][23][24] Despite numerous leads, the reported findings are somewhat inconsistent and the core regions associated with the pathogenesis of schizophrenia still remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired WM is a well-documented symptom in schizophrenia and arguably a core feature of the disease. Many studies investigating WM deficits in schizophrenia focus on the dorsolateral prefrontal cortex (dlPFC), a region implicated in executive functions, goal-directed planning, and inhibition (Jansma et al, 2004;Manoach et al, 2000;Potkin et al, 2009). However, the direction of dlPFC findings has been inconsistent across studies, which have demonstrated both diminished and enhanced dlPFC activation in schizophrenia (Carter et al, 1998;Manoach et al, 1999;Potkin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, WM function depends not only on activation of dlPFC and other nodes within the frontoparietal control network (FPCN) but also on deactivation of the default mode network (DMN; Anticevic et al, 2010). Numerous recent studies have identified altered DMN activation and connectivity in schizophrenia (Kim et al, 2009;Meda et al, 2009), complementing a large volume of work implicating FPCN dysfunction (Karlsgodt et al, 2007;Manoach et al, 2000;Minzenberg et al, 2009;Potkin et al, 2009). However, the relationship between WM deficits and both task-related activation and intrinsic network connectivity remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%